1999
DOI: 10.1046/j.1365-2796.1999.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary haemorrhagic telangiectasia: a population‐based study of prevalence and mortality in Danish patients

Abstract: Abstract. Kjeldsen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
285
1
26

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(318 citation statements)
references
References 26 publications
6
285
1
26
Order By: Relevance
“…Careful epidemiological studies reveal that it affects approximately 1 in 5,000 individuals, 4,5 with regional differences, 6 and isolated communities displaying higher prevalences due to founder effects. 7 8 HHT was first described as a familial disease characterised by severe recurrent nasal and gastrointestinal bleeding with associated anaemia, and visible dilated blood vessels (telangiectasia) on the lips and finger tips.…”
Section: Overview Of Hhtmentioning
confidence: 99%
“…Careful epidemiological studies reveal that it affects approximately 1 in 5,000 individuals, 4,5 with regional differences, 6 and isolated communities displaying higher prevalences due to founder effects. 7 8 HHT was first described as a familial disease characterised by severe recurrent nasal and gastrointestinal bleeding with associated anaemia, and visible dilated blood vessels (telangiectasia) on the lips and finger tips.…”
Section: Overview Of Hhtmentioning
confidence: 99%
“…epistaxis, telangiectasia, visceral lesions, and a family history with HHT, should be present in order to ensure the diagnosis. While the cutaneous and mucocutaneous manifestations have mostly a relative good prognosis, the involvement of the visceral organs, if untreated, can trigger mortality (Kjeldsen et al, 1999;Shovlin and Letarte, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic manifestation of HHT is estimated to affect about 8 to 30% of the patients (Reilly and Nostrant, 1984;Bauer et al, 1995;Kjeldsen et al, 1999). The hepatic vascular malformation can be diagnosed by ultrasound (Caselitz et al, 2003) and is mostly associated with fibrosis and/or atypical cirrhosis (Reilly and Nostrant, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate as a direct result of the disease is about 36% (Sawabe et al 2001). Furthermore, Kjeldsen et al 1999 reported an increased mortality among young HHT patients when compared with those of patients older than 60 years.…”
Section: Introductionmentioning
confidence: 99%